Modeling organ-specific vasculature with organ-on-a-chip devices. (5th November 2018) - Lin, Dawn S Y; Guo, Feng; Zhang, Boyang
Abstract: Organ-on-a-chip devices, also known as microphysiological systems, have gained significant attention in recent years. Recent advances in tissue engineering and microfabrication have enabled these devices to provide more precise control over cellular microenvironments to mimic the tissue-level or organ-level function of the human body. These more complex tissue models can provide either an improvement in the functional expression and maturation of cells or an avenue to probe biological events and function that would otherwise be difficult to visualize and mechanistically study. This high-value information, when complimented with the existing gold-standards of cell-based assays and animal models, could potentially lead to more informed decision-making in drug development. A prevalent biological component in many organ-on-a-chip devices is an engineered vascular interface that is present in almost all organs of the human body. The vasculature and the vascular interface are particularly susceptible to biomechanical forces, they function as the conduits for inter-cellular and inter-organ interactions, and regulate drug transport. In this review, we examine the various approaches taken to model the human vasculature with an emphasis on the engineering of organ-specific vasculatures, and discuss various challenges and opportunities ahead as the field advances.